KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS ROWOSARI SEMARANG (ANALISIS KEPADATAN VEKTOR DAN FAKTOR LINGKUNGAN) - Saripudin, Aip; Martini, Martini; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat, 2019)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted by the Aedessp Mosquito. The Incident Rate (IR) in the Rowosari Health Center area in 2018 is still high, which is 98/100,000 residents. This study purpose to analyze the correlation between the rate of larvae (ABJ) and several environmental factors with the incidence of dengue in the work area of Rowosari Public Health Center, Semarang City. The research is a descriptive study with a cross-sectional approach, carried out by the analytic survey method. The sample in this study was houses located in 5 urban villages in the Rowosari health center area chosen by purposive sampling method. The results of this study indicate that the Rowosari Health Center work area has a House Index value (17.5%), Container Index (5.7%), Breteau Index (19.5%) with density figure 2-5. The results of the Pearson correlation test showed no significant correlation between House Index (p = 0.126), Container Index (p = 0.494), Breteau Index (p = 0.094), population density (p = 0.919), temperature (p = 0.384), humidity (p = 0.229) with the incidence of DHF in the Rowosari health center work area. It is recommended that the community routinely clean containers as an effort to improve ABJ and conduct PSN regularly and thoroughly.